Design Of a Semi-Automatic Hand Line (Hand Line) For Semi-Automatic Squid in Wangi-Wangi Selatan Sub-District, Wakatobi District - Suwardi, Surahman; Baskoro, Mulyono; Iskandar, Didin Konarudi (International Journal of Marine Engineering Innovation and Research, 2025)
The amount of energy drained on fishermen when catching and using traditional squid fishing gear takes a long time, affecting fishermen's income. This research aims to design a semi-automatic squid fishing rod and determine the efficiency of using the new design of semi-automatic squid fishing gear. This research was conducted in the South Wangi-Wangi District, Wakatobi Regency, Southeast Sulawesi Province, from December 2023 to January 2024. The research method used was experimental fishing, which was used to design a semi-automatic fishing rod to know the effect of using semi-automatic fishing gear on catches. The construction of the semi-automatic squid fishing rod is by the planned design and is technically feasible to use. The productivity of the research shows that from the weight of the semi-automatic squid fishing rod catch of 36.02 kg, the number of 459 tails during 16 trips. The catch of traditional squid long line with a total weight of 34.76 kg and 511 tails during 16 trips. The results of statistical tests using t-test analysis show a difference that does not significantly affect the results of both fishing gears.